GAYA STILISTIKA PUISI â€œPEREMPUAN SELALU INGATâ€ KARYA DIAN RENNUATI: KAJIAN KERELEVANSIAN DENGAN PEMBELAJARAN BAHASA INDONESIA DI SMA - Hidajati, Enny (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2020)
Dian Rennuati is a doctor and poet from Palembang. Dian is known to have a style of language (stylistic) which is very beautiful from the point of women. The poem under study entitled